Two-step cascades of the 187W compound nucleus g-decay - Sukhovoj, Anatoly M. (Array, 2008)
Summary: Two-step cascades from the 186W(n,2g)187W reaction have been studied in the g-g coincidence experiment carried out in Rez. Their total intensity is evaluated with respect to the final level of cascades at » 1.9 MeV. The processes of the cascade g-decay of this nucleus, like of all nuclei previously studied in analogous experiments, can not be described without taking into account the influence of nuclear structure at energies lower than at least a half of the neutron-binding energy. The decay scheme of 187W, including 386 cascades, is determined up to the excitation energy ~ 3 MeV. It contains data about 196 excited levels of this nucleus with the most probable spins 1/2 and 3/2. As in the earlier studied nuclei, the population of the intermediate levels by the most intense cascades may indicate a harmonic character of the states involved